2011
DOI: 10.4049/jimmunol.1101406
|View full text |Cite
|
Sign up to set email alerts
|

AID Binds Cooperatively with UNG and Msh2-Msh6 to Ig Switch Regions Dependent upon the AID C Terminus

Abstract: Activation-induced cytidine deaminase (AID) is induced in B cells during an immune response and is essential for both class switch recombination (CSR) and somatic hypermutation (SHM) of antibody genes. The C terminal 10 amino acids of AID are required for CSR but not for SHM, although their role in CSR is unknown. Using retroviral transduction into mouse splenic B cells, we show that the C terminus is not required for S region DSBs, and therefore functions downstream of DSBs. Using chromatin immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 72 publications
8
77
1
Order By: Relevance
“…2A), suggesting that increased UNG binding occurs upon AID-induced damage response in agreement with previous reports (32,36). Next, we examined the effect of UNG deficiency on the recruitment of Polβ, XRCC1, FEN1, and PARP1, after confirming their normal expression in UNG −/− cells (Fig.…”
supporting
confidence: 72%
“…2A), suggesting that increased UNG binding occurs upon AID-induced damage response in agreement with previous reports (32,36). Next, we examined the effect of UNG deficiency on the recruitment of Polβ, XRCC1, FEN1, and PARP1, after confirming their normal expression in UNG −/− cells (Fig.…”
supporting
confidence: 72%
“…Biochemical Properties of AID C-terminal Deletion MutantsThe C-terminal region binds proteins targeting AID to Ig switch region DNA (28,29). Two naturally occurring mutations causing a loss of 9 and 17 C-terminal amino acids of AID (⌬C 9 and ⌬C 17 ) were found in HIGM-2 patients (14); the patient with ⌬C 17 also has an insertion in the C-terminal region (14).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the C terminus is essential for binding proteins such as UNG, MSH2, 14-3-3, and DNA-PK cs required to target AID to switch-region (28,29,36). For the HIGM-2 C-terminal mutants, although CSR is absent, SHM is almost normal (14,30), suggesting that AID retains a considerable level of C deamination activity when as many as 17 C-terminal amino acids have been removed.…”
Section: Structural Evaluation Of Higm-2 Point Mutants and C-terminalmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results in vitro and in vivo indicate that UNG is not rate limiting for CSR. Interestingly, published experiments using the same retroviral delivery strategy and assay as us showed that overexpressed AID in Aid 2/2 Msh2 2/2 B cells produced IgG1 CSR levels that were ∼50% of those it produced in Aid 2/2 B cells (39), raising the possibility that MSH2/MSH6 could be rate limiting.…”
Section: Ung Is Not Limiting For Csrmentioning
confidence: 99%